Understanding the Factors that Influence the Intention of Kuwaiti Entrepreneurs to use Technology Using the UTAUT Model - Almas, Ali (2024)
Financial literacy has risen dramatically across the board over recent times. After this shift, people began taking more control over their financial management by implementing budgetary planning, saving strategies, and investment tactics. It is essential to gauge the public’s enthusiasm towards cutting-edge technology during its development. This investigation focuses on determining the contributing elements that shape the acceptance and utilization of a digital financial literacy app among workers from diverse social and economic backgrounds in Kuwait. This study constructed the proposed model’s six primary constructs based on the existing frameworks of TAM, UTAUT, and Usability models. The factors to be considered in this study are as follows: firstly, performance expectations; secondly, expected effort; thirdly, social influence; fourthly, resources and cost; fifthly, subjective happiness; and finally, deliberate conduct. The statistical assessment of all hypotheses in this study was conducted using SmartPLS methods. According to this study, it is recommended that workers with lower socioeconomic backgrounds should not receive financial literacy education using digital platforms due to their limited proficiency in technology. The UTAUT model has been commonly used in gauging the level of technology implementation. The UTAUT framework employs four key factors to assess the diffusion of emerging technologies. The UTAUT model has been widely utilized to assess novel technologies, utilizing four key elements to delineate public reception of emerging gadgets and systems: The outcomes are anticipated to enhance women’s impact across various domains within society. The potential benefits derived from the utilization of extensively researched technology are predicated upon optimistic assumptions. A quantitative assessment of the effort necessary to utilize the technology effectively. One determinant that can impact the broad acceptance of technology is social influence, which pertains to the manner in which individuals are influenced to utilize it. Facilitating conditions pertain to evaluating the technological infrastructure’s extent and effectiveness in facilitating and streamlining the utilization of the technology. This study’s findings suggest that a digital platform may not be the most efficient means of conveying financial literacy to individuals from lower-middle socioeconomic backgrounds due to their limited familiarity and comfort with technology. This methodology is employed to ascertain the potential of digital applications in facilitating the enhancement of individuals’ financial literacy comprehension, particularly with regard to gender. Using digital applications in financial literacy training has contributed to enhanced knowledge among Kuwaiti entrepreneurs regarding fund management.